High technologies as a way of transformation of media discourse - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The article analyzes the role of high technologies in the processes of transformation of media discourse. The positive and negative consequences of the introduction of modern, in particular, information and communication technologies, in the activity of the media are revealed. The peculiarities of influence of these technologies on the social and individual consciousness are studied.